Sarf Ibtida’iy Assessment with Opexams Among University Students Based on Artificial Intelligence | Taqyim al-sarf al-ibtida'i bi-Ub-Aikzam lada al-talabah al-jami'iyyah 'ala asas al-dhaka' al-istina'i - Akhmad Yusuf Isnan Setiawan; Inayah Inayah; Muhammad Izzul Muhtar; Feri Aditia Saputra; Asma’ Na’im Jamil Abu Samra (Al-Ta'rib)
This study aims to characterize Opexams and evaluate their effectiveness on the learning outcomes of shart-ibtida’iy (basic drainage). Using a quantitative approach with a pre-experimental design, the study involved 37 students from Walisongo State Islamic University as the sample, selected through purposive sampling. Data were collected using tests, observation sheets, and questionnaires, then analyzed using empirical analysis and hypothesis testing, including a one-sample t-test. The findings indicate that the basic drainage assessment was conducted using 100 multiple-choice questions designed through Opexams based on the Generate framework. The total score obtained was 8,335, with a median of 220, a mean of 225.27, a highest score of 360, and a lowest score of 115. The variance was 4,379.657, and the standard deviation was 66.18. A significance level of 5% was used with 36 degrees of freedom (df). The t-test result showed a value of 1.4, meaning T = 1.4 < TTable = 2.021. Consequently, the null hypothesis (Ho) was accepted. This indicates that the learning outcomes for basic drainage did not improve, suggesting that the assessment using Opexams was ineffective in enhancing students' learning outcomes.